Optimization of scanning strategy of digital Shack–Hartmann wavefront sensing - Li, Xiang (2013)
In the traditional Shack–Hartmann wavefront sensing (SHWS) system, a lenslet array with a bigger configuration is desired to achieve a higher lateral resolution. However, practical implementation limits the configuration and this parameter is contradicted with the measurement range. We have proposed a digital scanning technique by making use of the high flexibility of a spatial light modulator to sample the reflected wavefront [LiX.ZhaoL. P.FangZ. P.TanC. S., “Improve lateral resolution in wavefront sensing with digital scanning technique,” in Asia-Pacific Conference of Transducers and Micro-Nano Technology (2006)]. The lenslet array pattern is programmed to laterally scan the whole aperture. In this paper, the methodology to optimize the scanning step for the purpose of form measurement is proposed. The correctness and effectiveness are demonstrated in numerical simulation and experimental investigation.